Effect of arsenic (III and V) on oxidative stress parameters in resistant and susceptible Staphylococcus aureus - Jelinkova, Pavlina; Vesely, Radek; Cihalova, Kristyna; Hegerova, Dagmar; Ananbeh, Hanadi Abd Alrahman Ali; Richtera, Lukas; Smerkova, Kristyna; Brtnicky, Martin; Kynicky, Jindrich; Moulick, Amitava; Adam, Vojtech (Environmental research. Section A, 2018)
The presented study deals with the observation of properties of methicillin-susceptible Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus (MRSA) in the toxic arsenic environment and influence of arsenic on antioxidant capacity. Two forms of arsenic (As(III), As(V)) with different concentrations were used for induction of the oxidative stress in tested strains. Microbiological methods showed that the growth inhibition of MSSA was higher than that of MRSA in presence of both arsenic ions. As(III) showed 24% and 33% higher anti-microbial effects than As(V) against MSSA and MRSA respectively. A similar result was found also in the experiment of reduction of biofilm-formation. By using spectrophotometry, it was revealed that As(III) induced higher antioxidant production in both bacterial cultures. Methicillin-susceptible S. aureus produced an app. 50 mg equivalent of gallic acid (GAE/1 mg of protein) and MRSA produced an app. 15 mg of GAE/1 mg of protein. The productions of metallothionein in MSSA and MRSA were decreased up to 62.41% and 55.84% respectively in presence of As ions. Reduction of As(III) and As(V) concentrations leads to a decrease in antioxidant production and increased the formation of metallothionein. All of these changes in the results were found to be significant statistically. Taken together, these experiments proved that in comparison with MSSA, MRSA is less susceptible not only to the antimicrobial effects of antibiotics but also against effects caused by metalloids, as arsenic. Thus, it can be stated that MRSA abounds with complex defensive mechanisms, which may in the future constitute significant problem in the efficiency of antibiotics alternatives as metal ions or nanoparticles.
Keywords: Methicillin-Resistant Staphylococcus aureus; Oxidative Stress; kyselina gallová; antioxidancia; Anti-Bacterial Agents; Arsenic; Staphylococcus aureus; mikrobiální testy citlivosti; methicilin rezistentní Staphylococcus aureus; antibakteriální látky; oxidační stres; Microbial Sensitivity Tests; Gallic Acid; Antioxidants; arsen